2012
DOI: 10.1007/s10433-012-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of care policy measures supporting older people: towards greater flexibility for carers?

Abstract: Originally part of the private domain of families, care of the older people is now the concern of public policy. Yet, in the European context of cost containment, it is not easy to make a case for increasing public support and the caring function of families remains prominent in social policy. In this paper, the authors question public policies around care of the older people in relation to both the needs of old people, but also those of adult children, mainly women, who work and provide care for their old par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
0
16
0
4
Order By: Relevance
“…The care policies of the Dutch welfare state are relatively generous, and the state has a main role in the regulation of cash payments, care leave and flexibility of working hours. In Italy, by contrast, the welfare state has a fairly minor role in long-term senior care, and care policies are not generous (Le Bihan and Martin 2012). As the authors show, welfare states also support such practices indirectly when they offer cash-for-care but with only low-level monitoring of the schemes by public authorities.…”
Section: Differences In the Main Types Of Care Employmentmentioning
confidence: 90%
See 2 more Smart Citations
“…The care policies of the Dutch welfare state are relatively generous, and the state has a main role in the regulation of cash payments, care leave and flexibility of working hours. In Italy, by contrast, the welfare state has a fairly minor role in long-term senior care, and care policies are not generous (Le Bihan and Martin 2012). As the authors show, welfare states also support such practices indirectly when they offer cash-for-care but with only low-level monitoring of the schemes by public authorities.…”
Section: Differences In the Main Types Of Care Employmentmentioning
confidence: 90%
“…Le Bihan and Martin found that in the Netherlands, care work is mainly formal employment, whereas in Italy the organisation of care relies strongly on undeclared employment of mostly female, migrant care workers in private households (Le Bihan and Martin 2012). According to the authors, differences in the generosity of states' senior-care policies are the main factor which explains such differences.…”
Section: Differences In the Main Types Of Care Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovisnost u starijoj dobi prepoznaje se kao socijalni rizik tek unatrag dva desetljeća, kada počinje intenzivnije razmatranje i provođenje reformi koje vode formaliziranju skrbi, odnosno raste javna uključenost u reguliranje, financiranje, organiziranje i pružanje skrbi starijima (Rostgaard i Zechner, 2012). Veća uloga države ogleda se u sve većem obuhvatu uslugama dugotrajne skrbi, prepoznavanju prava na skrb kao socijalnoga prava, uvođenju osiguranja za dugotrajnu skrb i/ili u priznavanju neformalne skrbi (vidi Schut i Van den Berg, 2010;Rostgaard i Zechner, 2012;Le Bihan i Martin, 2012;Ranci i Pavolini, 2013). 1 Priznavanje neformalne skrbi vodi tzv.…”
Section: Trendovi Reformi Sustava Skrbi Za Starije U Europskim Zemljamaunclassified
“…Posebice raste popularnost shema kojima se osigurava naknada za skrb (eng. cash-for-care; da Roit, Le Bihan i Österle, 2007;da Roit, 2012;Le Bihan i Martin, 2012), ali i dopusti mogućnost prilagodbe radnoga vremena zbog pružanja dugotrajne skrbi (Le Bihan i Martin, 2012). Poluformalizacija skrbi čini granice između uobičajenih oblika skrbi, formalnih i neformalnih, plaćenih i neplaćenih, nejasnima (Pfau-Effinger i Geissler, 2005), dok u nekim zemljama (npr.…”
Section: Trendovi Reformi Sustava Skrbi Za Starije U Europskim Zemljamaunclassified